A Structured Narrative Literature Review of Approved Mental Health Professional Detention Decisions: An Infusion of Morality. Issue 4 (21st August 2020) - Simpson, Matthew
Abstract : In England and Wales, Approved Mental Health Professionals (AMHPs) may make applications to detain people in hospital under the Mental Health Act (MHA) 1983 as amended 2007. This paper seeks to establish what the available academic literature has to say about AMHP detention decisions. A structured narrative literature review was conducted with the identification of twenty-five included texts that were thematically analysed interpretively. Risk, accountability, and morality are identified as dominant themes in this review. Risk is prominent, but on closer inspection risk is infused with morality. Morality is the merging of the personal and professional domains, the use of self to understand another. Accountability is situated between morality and risk, inextricably linked on both sides with authors identifying a fear of responsibility for adverse consequences. Sub-themes of emotions, intuition, uncertainty, coercion, and alternatives (to admission to hospital) were also found. Analysis of nearly thirty years of literature regarding ASW/AMHP detention decisions tells us that they are not based solely on technical judgements; morality permeates the decision. The literature is justified in evincing risk in detention decisions, but the prominence of risk overshadows accountability and belies the influence of morality.